The enrichment of Kelulut (Trigona spp.) feeding plants for its sustainability in mangrove ecotourism Beras Basah Village, Langkat Regency, North Sumatra, Indonesia - Dewi, Rita Rosmala (Talenta Publisher Universitas Sumatera Utara, 2025)
The cultivation of Trigona honey bees by the